Structural change and poverty reduction in Ethiopia: Economy-wide analysis of the evolving role of agriculture - Dorosh, Paul A.; Thurlow, James; Kebede, Frehiwot Worku; Ferede, Tadele; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
This paper explores these issues for Ethiopia utilizing an economy-wide computable general equilibrium (CGE) model based on a detailed social accounting matrix (SAM). We present the results of four alternative investment scenarios -- faster investment in i) cities; ii) crop agriculture; iii) the rural non-farm sector and agro-industry; and iv) livestock. The simulations suggest that investments in cities generate faster economic growth and structural transformation. However, given the large share of the population with incomes linked to agriculture and the rural economy, investments in the rural economy are likely to continue to be more pro-poor than urban public investments through the mid-2020s. After the mid-2020s, investments in cities become more pro-poor. In short, though rapid economic growth and structural transformation have diminished the relative importance of the agricultural sector in Ethiopia’s economy, continued public investments in agriculture and the broader agri-food system remain crucial for equity and poverty alleviation in Ethiopia, as well as for reducing food import dependency.